1982
DOI: 10.1523/jneurosci.02-02-00225.1982
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of somatostatin-like immunoreactivity in the rat central nervous system by cysteamine

Abstract: Selective neurotoxins have been of value in providing a means for specifically interfering with the actions of endogenous neurotransmitter candidates. Others have shown cysteamine (CSH) to deplete the gastrointestinal tract and hypothalamus of rats of immunoreactive somatostatin, suggesting a toxic action of that compound directed against somatostatin-containing cells. The present study further defines the actions of cysteamine on somatostatin in the central nervous system. (CNS). Cysteamine hydrochloride admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(36 citation statements)
references
References 22 publications
7
29
0
Order By: Relevance
“…Ablation in SST ‫מ/מ‬ mice and pre-training depletion with cysteamine, in particular due to its long half-life (Sagar et al 1982), are likely to interfere with somatostatinergic processes during both memory acquisition and memory consolidation (Abel and Lattal 2001;Anagnostaras et al 2001;Rodrigues et al 2004). In our experiments, only pre-training, but not immediate post-training, infusion of cysteamine selectively interfered with contextual fear memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation in SST ‫מ/מ‬ mice and pre-training depletion with cysteamine, in particular due to its long half-life (Sagar et al 1982), are likely to interfere with somatostatinergic processes during both memory acquisition and memory consolidation (Abel and Lattal 2001;Anagnostaras et al 2001;Rodrigues et al 2004). In our experiments, only pre-training, but not immediate post-training, infusion of cysteamine selectively interfered with contextual fear memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…in rats pretreated with cysteamine (Cys), which depletes endogenous somatostatin (SRIH) stores [17]. Reportedly, SRIH participates in the inhibitory control of gastric acid secretion, and binding sites for the GHS have been detected on hypothalamic SRIH neurons [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore in vitro studies using pituitary tumor cells have demonstrated that somatostatin can direc tly inhibit ACTH secretion [I, 12, 14, 20. 21], Somatostatin may thus be one of many factors regulating pituitary ACTH secretion (see review by Axelrod and Reisine [I]).To determine whether somatostatin systems might play a role in the dexamethasone-induced suppression of the HPA axis in vivo, the effect of pretreatment with cys teamine, a drug which reduces somatostatin levels [2,16,24,26,28,29,31], on the dexamethasone-induced sup pression of plasma corticosterone levels was investigated in the rat. …”
mentioning
confidence: 99%